IL‐15 and RANKL Play a Synergistically Important Role in Osteoclastogenesis. Issue 4 (20th December 2016) - Okabe, Iichiro; Kikuchi, Takeshi; Mogi, Makio; Takeda, Hiroaki; Aino, Makoto; Kamiya, Yosuke; Fujimura, Takeki; Goto, Hisashi; Okada, Kosuke; Hasegawa, Yoshiaki; Noguchi, Toshihide; Mitani, Akio
ABSTRACT: Interleukin‐15 (IL‐15), a cytokine secreted by several cell types, has important physiological roles in the activity, proliferation, and viability of immune cells. It has both chemoattractant and proinflammatory properties, and may promote bone destruction. A previous study has shown that IL‐15 alone exerts no effect on osteoclastogenesis. Therefore, the current study addressed the synergistic effect of IL‐15 on osteoclast formation using RAW264.7 (RAW) cells by co‐stimulation with receptor activator of nuclear factor (NF)‐κB ligand (RANKL) that has a major role in osteoclastogenesis involving the pathogenesis of rheumatoid arthritis and periodontal disease. Co‐stimulation of RAW cells by IL‐15 and RANKL significantly increased the gene expression of osteoclast differentiation and osteoclastogenesis markers compared with stimulation by RANKL or IL‐15 independently as evaluated by tartrate‐resistant acid phosphate‐positive cell numbers, the fusion index, a pit formation assay with Alizarin red staining (calcification estimation), and quantitative polymerase chain reaction. Phosphorylation of extracellular signal‐regulated kinase (ERK), c‐jun N‐terminal kinase, p38 mitogen‐activated protein kinase, and NF‐κB was significantly increased by RANKL and IL‐15 ( P  < 0.05) compared with RANKL alone. In addition, these differentiation activities induced by RANKL and IL‐15 were comparatively suppressed by inhibition of ERK, suggesting that this synergistic effect on osteoclastogenesis is mainly mediated by ERK. Taken together, our results demonstrate that IL‐15 and RANKL induce osteoclastogenesis synergistically, and IL‐15 might play a novel and major role in destructive inflammatory bone diseases. J. Cell. Biochem. 118: 739–747, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Interleukin‐15(IL‐15) and receptor activator of NF‐κB ligand induce osteoclastogenesis synergistically, and IL‐15 plays a novel and important role in destructive inflammatory bone disease.